2021
DOI: 10.3126/jgmcn.v14i1.31474
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing job retention and satisfaction among nurses in tertiary level hospital

Abstract: Introduction: Retention of nurses in any health care facilities is essential for maintaining quality nursing care. Nurses’ job satisfaction is an important issue to retain nurse in same organization. The study aimed to assess factors influencing job retention and satisfaction among nurses. Methods: The descriptive cross-sectional study was done among 125 nurses working in Manipal Teaching Hospital. Purposive sampling technique was used to select the sample. The semi structured self-administered questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…On the other hand, a sense of dissatisfaction can result in burnout, reduced efficiency, and a desire to depart from the occupation (Zhang, Feng, et al, 2021; Zhang, Zuo, et al, 2021). Based on empirical evidence, it can be inferred that job satisfaction correlated positively with nurse retention in various healthcare settings (Putra et al, 2020; Rana & Shakya, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a sense of dissatisfaction can result in burnout, reduced efficiency, and a desire to depart from the occupation (Zhang, Feng, et al, 2021; Zhang, Zuo, et al, 2021). Based on empirical evidence, it can be inferred that job satisfaction correlated positively with nurse retention in various healthcare settings (Putra et al, 2020; Rana & Shakya, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has dedicated significant attention to the examination of work-family conflict [17][18][19] and the role of social support [20]. A substantial body of nursing literature in Nepal has conducted comprehensive investigations on the topic of work satisfaction [21][22][23][24][25][26][27]. For example, a research conducted by Shrestha et al [21], showed that individuals who viewed themselves as significant assets to the healthcare system reported greater levels of work satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, in private teaching hospitals, nurses were encouraged to stay primarily by opportunities for professional growth, fringe benefits, and positive relationships with colleagues [24]. There are factors with significant role in the retention of nurses, which included, punctual disbursement of salaries, positive interpersonal dynamics within the workplace, a feeling of organizational pride, sufficient provision of supplies and equipment, the maintenance of a safe working environment, possibilities for professional growth, and the presence of a supportive matron [25]. However, these studies have not investigated the issues, such as work-family conflict and social support that influence the levels of job satisfaction among nurses in Nepal.…”
Section: Introductionmentioning
confidence: 99%